1991
DOI: 10.1073/pnas.88.20.8996
|View full text |Cite
|
Sign up to set email alerts
|

Human auditory evoked gamma-band magnetic fields.

Abstract: We have discovered a ca. 40 (22,23) have identified a transient electric GBR locked in time to the onset of auditory stimuli that increases in amplitude as the stimulus rate is decreased below one per second. We report here measurements of a comparable magnetic GBR, using a new-generation large-array biomagnetometer. Large-array magnetic measurements allow accurate and reliable localization of the source of the magnetic GBR in relation to the better studied M100 and M200 slowwave (low-frequency; see below) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
182
1
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(209 citation statements)
references
References 23 publications
24
182
1
2
Order By: Relevance
“…Note first that the gamma-band response contributes a large positive-going wave to ERP component Pa, which corresponds to activation of the primary auditory cortex (Kraus et al, 1982;Woods et al, 1987). This is consistent with the observation that the early stimulus-evoked gamma band activity arises from sensory cortical regions (Barth and MacDonald, 1996;Pantev et al, 1991). Note that the peak amplitude of this waveform receives relatively little contribution from beta band activity, which was shown in the present study to be particularly sensitive to ISI.…”
Section: Comparison With Previous Studies Of Sensory Gatingsupporting
confidence: 92%
See 1 more Smart Citation
“…Note first that the gamma-band response contributes a large positive-going wave to ERP component Pa, which corresponds to activation of the primary auditory cortex (Kraus et al, 1982;Woods et al, 1987). This is consistent with the observation that the early stimulus-evoked gamma band activity arises from sensory cortical regions (Barth and MacDonald, 1996;Pantev et al, 1991). Note that the peak amplitude of this waveform receives relatively little contribution from beta band activity, which was shown in the present study to be particularly sensitive to ISI.…”
Section: Comparison With Previous Studies Of Sensory Gatingsupporting
confidence: 92%
“…Further supporting evidence includes the finding that gamma oscillations are generally localized to specific sensory cortical regions (Barth and MacDonald, 1996;Pantev et al, 1991;Pantev, 1995) whereas beta activity exhibits more widespread expression across cortex and more robust synchronization between cortical regions including association areas (Roelfsema et al, 1997;von Stein et al, 1999). Nevertheless, applicability of this theory to a general neural model of stimulus-driven salience processing requires empirical demonstrations that other relevant properties, such as novelty and ISI, also appropriately modulate oscillatory neuron population activity, especially in the beta band.…”
Section: Introductionmentioning
confidence: 97%
“…The latency range of the observed additional activity raises the question of its relationship with the transient gamma band response (GBR) which has been recently discovered by electric (Makeig and Galambos, 1989) and magnetic (Pantev et al, 1991) encephalographic studies. It has been suggested that this response does not participate in the generation of the 40 Hz-SSR since these neural activities originate from separate cortical sources (Pantev et al, 1993).…”
Section: Comparison Between Mlrs Lcrs and Mlcrsmentioning
confidence: 99%
“…Our findings of significant differences of gamma band activity in the lag time of 2-4 ms coincides directly with the thalamocortical conduction time (Albe-Fessard et al 1986;Allison et al 1991;Pantev et al 1991;Ribary et al 1991). We also demonstrated significant differences for gamma oscillations in the lag time of 15 ms, which refers to perceptual binding occurring in a time segment of &15 ms (Joliot et al 1994;Llinas and Ribary 2001) on the basis of synchronization (i.e.…”
Section: Discussionmentioning
confidence: 57%